A zálogjog és a hitelbiztosítéki nyilvántartás - Ferenczi, Fanni (Debreceni Jogi Műhely, 2016)
Analyzing th esystem of mortgage we must reach back to the Roman Law. At that era it had been possible to pledge liabilities, rights and moreover aggregated asset, property. Mortgage is a long term institute of Hungarian Private Law as well. Paragraphs 251 – 269 of Act IV of 1959 on the Civil Code of the Republic of Hungary regulates mortgage in the Law of Obligations, placed among collaterals. In the last two decades the old Civil Code of the Republic of Hungary has been modified twice. Act V of 2013on the Civil Code of the Republic of Hungary weakens but definitely rewritten the principles of lending. Regulation of mortgage and the system of chattel mortgage registry has significantly changed. Several novelty has been introduced therefore the system of chattel mortgage registry was reformed too. Detailed regulations of credit guarantee registry in Act CCXXI of 2013 and Act 18/2014. (III. 13.) KIM has also been accepted correspondingly to the previous changes.